Ensaios sobre exportações por intensidade tecnológica e o crescimento econômico dos estados brasileiros - Teixeira, Felipe Orsolin (2018)
The aim of the present work, divided into two essays, is to perform an analysis of exports by levels technological intensity and economic growth of the Brazilian States between the years of 1998 and 2014. The first essay verifies, through the theoretical framework of the Multisectoral Thirlwall's law and the use of panel data model, if the growth of Brazil presented to your balance of payments constraint and, also, what are the elasticities of the products that are traded with the external market. The second essay is inserted in the debate between specialize or diversify the productive structure and, for this, the PRODY and EXPY indexes are used, which allow to verify the implicit productivity of the products and the especialization of the export basket of Brazilian States, respectively. In this way, through the use of econometric models, the second essay aims to demonstrate the relationship that the especialization of the different levels of technological intensity of the exports has with economic growth. The main results of the first essay indicated that the growth of the brazilian economy was restrict to your balance of payments during the analyzed period and that the products with greater technological intensity showed a higher-income elasticity of demand for exports. As the main results of the second essay, it has the specialization of the high-technology sector showed a positive relation with the income of level in the years of 1998 and 2014, and that the especialization of other sectors of technological intensity presented negative relation with the level of income for the year of 2014. It is also verified that the specialization of low-tech sector and non-industrial products exhibit negative correlation with the specialization of all other sectors, indicating little chaining power.